Extent of implementation of in-service education principles at the Dacca Refresher Course Training Center, Pakistan, and its implications for the improvement of the in-service education progran there - Mannan, Muhammad Abdul 1932- ([Quezon City s.n.], 1967)
This is an investigation of the extent of the implementation of in-service education principles at the Dacca Refresher Course Training Center, Pakistan. The implications for the improvement of the in-service education program at the said center were drawn.
Thesis (M.Ed.)--University of the Philippines
Keywords: Teachers -- In-Service training -- Pakistan